Ethical and professional concerns in research utilisation: Intentional rounding in the United Kingdom - Snelling, Paul C (Nursing ethics, 2013)
Intentional rounding, a process involving the performance of regular checks on all patients following a standardised protocol, is being introduced widely in the United Kingdom. The process has been promoted by the Prime Minister and publicised by the Chief Nursing Officer at the Department of Health as well as by influential think tanks and individual National Health Service organisations. An evidence base is offered in justification. This article subjects the evidence base to critical scrutiny concluding that it consists of poor quality studies and serial misreporting of findings and a failure to consider wider concerns, including transference of evidence to differing health-care systems, and the conflation of perception and quality of care. Political promotion and wide implementation of intentional rounding despite the flimsy and questionable evidence base raise questions about the use of evidence in ethical nursing practice and the status of nursing as an autonomous profession.